Politeness maxim representations in Javanese culture: Revitalization strategy to reduce verbal sexual violence - Sabrina, Arini; Tur, Ajar Pradika Ananta (Journal of Religion and Linguistics, 2025)
Yogyakarta Province one of which is regarding verbal violence. On the one hand, this fact is truly ironic in light of Yogyakarta's extraordinary reputation as a cultural diorama in Indonesia, which is particularly evident in its politeness identity representations. Conversely, Yogyakarta's Javanese propriety culture called as unggah-ungguh serves as a fundamental potential safeguard for its society through the incorporation of local cultural elements. This unique cultural politeness is also comparable to Leech's Six Maxims of Politeness, which include Tact Maxim, Generosity Maxim, Approbation Maxim, Modesty Maxim, Agreement Maxim, and Sympathy Maxim. This research discusses the relationship between these Maxims and Javanese parenting patterns explained in the books published by the Department of Women's Empowerment, Child Protection, and Population Control of Yogyakarta for teachers and parents in Yogyakarta regarding the importance of polite communication and good behavior that is rooted in Javanese tradition. If the action is strengthened in school to university levels, added with optimal support echoed in the family and community, verbal sexual violence can hopefully diminish.